Outcomes of event-free survival in patients with Wilms tumor undergoing preoperative chemotherapy. Analysis of lymph-node yield in a single-center cohort. Issue 2 (April 2021) - Flores, Paula; Cadario, Martin; Strambach, Julieta; Sanjuanelo, Mariana; Saleme, José Maria; Paz, Enrique; Cacciavillano, Walter; Felizzia, Guido; Galluzzo, Laura; Corbetta, Juan Pablo
Summary: Introduction: The clinical value of lymph node sampling in Wilms tumor (WT) lies in its ability to accurately determine lymph node (LN) involvement. LN yield (LNY) is used as a valuable tool to measure LN retrieval, and a minimum of 6 LNs is one of the current recommendations. In patients who are managed with the SIOP strategy, preoperative chemotherapy decreases the retrieval of LN during surgery resulting in lower LNY values. Purpose: To determine the mean LNY and to analyze survival outcomes in patients with WT who underwent preoperative chemotherapy at a single center. Methods: We performed a retrospective chart review of all patients between 6 months and 12 years of age with unilateral WT who underwent preoperative chemotherapy between 2010 and 2018. Patients with bilateral WT or without preoperative chemotherapy were excluded. Collected data included: demographics, tumor volume, tumor histopathology, number of LNs collected (LNY), presence or absence of tumor in the retrieved LNs, and disease stage according to these results. Kaplan Meier curves were calculated to estimate 5-year event-free survival (EFS) and overall survival (OS). Results: 95 patients with a median follow-up of 25 months were included in the study. A total of 19 patients underwent laparoscopic surgery. Mean LNY for the entire cohort was 3.26 (95% CI, 2.4–3.6; SD, 3.62). Six patients (6.3%) had at least one positive LN. The estimated 5-year OS was 89.3% (95% CI, 82.1%–96.5%). EFS was 79.8 (95% CI, 74.8%–84.8%). Recurrence rate was 20% (n: 19). Four patients (4.2%) developed local recurrence and 15 patients (15.7%) developed pulmonary recurrence. The initial mean LNY in patients that relapsed was 4.16 (95% CI, 2.2–5.8; SD: 4.18), which was higher than in patients who did not relapse (LNY: 3; 95% CI, 2.33–3.67; SD, 3.39). No recurrences or deaths occurred in the laparoscopic group. Discussion: The identification of a minimum LNY (i.e. threshold) to minimize the risk of harboring occult metastatic disease has been proposed to standardize the surgical procedure. Preliminary results in this study suggest that a limited LNY with acceptable survival outcomes is a possible scenario in patients treated according to the SIOP protocol. Systematic LN sampling to reduce the rate of false negatives is still strongly recommended. Conclusion: Our cohort presented with a relatively low LNY compared to standard recommendations. Our EFS, however, remained acceptable. Multivariate analysis would be necessary to determine the actual role of LN sampling as an isolated prognostic factor in unilateral WT.